PENGARUH KONSELING EKOLOGI BRONFENBRENNER DALAM PENINGKATAN KETERAMPILAN SOSIAL MAHASISWA IAI DARUSSALAM BLOKAGUNG - baroroh, nurin; al-musafiri, rizkon (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Problems that arise in relation to students related to ecological counseling are counseling places that are less representative as locations for counseling solutions. IAIDA students as santri students have various problems that must be resolved. However, unfavorable environmental conditions make the problem even more severe. Complex student problems result in a lack of social skills from students. They are required to graduate immediately so that they forget the essence of lectures, namely developing social skills. This study aims to accurately describe the conditions or situations that exist in a population or sample with the exception of explaining or finding causation between the variables studied. The research design used a One Shoot Case Study which was carried out in one experimental class. The results of the hypothesis test obtained a tcount value of 3,204 and a significance of 0.840. Look for ttable at a significant level of 5% with degrees of freedom (df) n-k-1 or 24-2-1 = 21. With a 2-sided test (significance = 0.05) the results obtained for ttable are 2.079. Because tcount (3.204) > ttable (2.079) then H0 is rejected. This means that Bronfenbrenner's ecological counseling has a significant effect on students' social skills.